2014
DOI: 10.1111/trf.12644
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in blood transfusion: an analysis of 244,013 hospitalizations

Abstract: Although there has been a reduction in the mean RBC units used, there has been an increase in the proportion of hospitalizations transfused. A better understanding of the indications for transfusion is required to facilitate the development of targeted blood conservation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 31 publications
3
44
0
Order By: Relevance
“…This increased focus was highlighted by the 2011 National Blood Collection and Utilization Survey in which approximately one‐third of hospitals responded that they were utilizing some elements of a blood conservation program . The National Blood Collection and Utilization Survey reported a 7.4% decline in the number of allogeneic RBCs transfused nationally compared to 2008, and similar declines have been observed in Canada and the United Kingdom …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This increased focus was highlighted by the 2011 National Blood Collection and Utilization Survey in which approximately one‐third of hospitals responded that they were utilizing some elements of a blood conservation program . The National Blood Collection and Utilization Survey reported a 7.4% decline in the number of allogeneic RBCs transfused nationally compared to 2008, and similar declines have been observed in Canada and the United Kingdom …”
Section: Discussionmentioning
confidence: 65%
“…Several studies have shown blood conservation programs to be effective in reducing blood utilization and healthcare costs in cardiac and orthopedic surgery . Recent studies have evaluated the impact of these programs on transfusion practice, and we recently reported no correlation between decreased RBC use and mortality across an entire hospital population . In this report, we examined trends in RBC utilization and mortality in patients previously studied in clinical trials as well as other subgroups.…”
mentioning
confidence: 99%
“…The Ottawa Hospital's Data Warehouse is a large data repository for the hospital's information systems that includes the hospital's administrative, laboratory, and discharge abstract information databases. The Data Warehouse is optimally structured for transfusion research, permitting identification of transfusion recipients, and tracking their use of hospital services and health outcomes …”
Section: Methodsmentioning
confidence: 99%
“…The majority of cases in our series involved transfusions in immunocompetent hosts. Although immunocompromised recipients comprised a considerable proportion in our cohort, the latter appeared no more enriched with such patients than other populations requiring transfusions, 34 (Table 6), and the immunecompromised proportion did not change in successive eras, with presumed more prevalent application of irradiation policies and universal leukoreduction. Our findings question whether, or to what degree, underlying immune deficiencies contribute to susceptibility to TA-GVHD and to what degree these are incidental surrogates of exposure opportunities to other drivers of risk.…”
Section: Org Frommentioning
confidence: 96%